THE EFFECT OF NASTY AND NON-NASTY MARRIED CELEBRITY ENDORSERS ON THE ATTITUDE, BRAND, AND PURCHASING INTENTION OF THE CONSUMER - Lina Lina (Journal of Indonesian Economy and Business (JIEB), 2009)
This research describes how Advertising Response Modelling (ARM) provides a framework to measure advertising performance by integrating several multiple measuresused in copy research. Several studies found that the use of celebrity endorsers is a popular execution device, but it is not without risk. The author reports the study examininghow the case of negative information about an endorser can affect three variables: attitude toward ads, attitude toward brand, and purchasing intention. The aims of this researchwere to measure the influence of negative traits of endorsers on consumers’ attitude toward the product, the brand, and the purchasing intention. Experimental research design was employed in this study. The participants in this research were students who are studying at Master of Economics Science, Gadjah Mada University, Yogyakarta. There were 100 participants out of 113 samples used as participants. Those participants were exposed to a printed advertisement of drinking product “Extra O2” brand. Then, they were also exposed to the case of negative information of the endorsers who have and have no nasty married. After that, the participants were asked to fill in self-administered and structured questionnaire. By using ARM and One-way ANOVA analysis, the research shows that endorsers without divorce problem has influenced positively the audience morethan that of endorser with nasty married. However, there are no significant differences between men and women in responding the advertising with nasty and non-nasty marriedendorsers. Keywords: Advertising Response Modelling (ARM), endorsers with nasty and without nasty married Attitude toward ads, attitude toward brand, and purchasing intention.